ARRIVAL OF COMPLEX TV IN TAMIL OTT SERIES: A STUDY OF SUZHAL - THE VORTEX - Pandian, Maruthu; M. R, Sathyaprakash (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The world of visual storytelling has taken many forms over the last century. The narrative approaches have constantly changed along with advancement of technology. This study attempts to look at how the 21st century’s prominent technological advancement, the internet, has influenced the script writing process and narrative techniques of television series. Using the poetics of complex TV, a textual analysis of the pilot episode of Suzhal - The Vortex was conducted. It is seen that the quintessential complex TV elements such as ambiguity, use of the anti-hero, and multiple plots, which existed in the West, have started to manifest in Tamil OTT series, with Suzhal - The Vortex serving as a microcosm of a larger trend.